Multiparty Alliances and Systemic Change: The Role of Beneficiaries and Their Capacity for Collective Action - Trujillo, Diana (Journal of business ethics, 2018)
The intensification of cross-sector collaboration phenomena has occurred in multiple fields of action. Organizations in the private, public, and social sectors are working together to tackle society’s most wicked problems. Some success has resulted in a generalized belief that cross-sector collaborations represent the new paradigm to manage complex problems. Yet, important knowledge gaps remain about how cross-sector alliances generate value for society, particularly to its beneficiaries. This paper answers the question: How cross-sector collaborations lead to systemic change? It uses a qualitative embedded case study design. I use two general cases of alliance-based interventions in the developing country Colombia. Embedded cases within each general case identify evidence of collective action capacity of the beneficiaries. Findings identify and explain alliances’ contributions to beneficiaries’ capacity building: brokering trust and creating spaces where beneficiaries develop an emergent collective action capacity. Alliances also enable beneficiaries to enact that capacity by building bridges, circulating capitals, and buffering relationships to protect people’s initiatives. Alliances and empowered collectives of beneficiaries produce systemic change using five mechanisms: brokering trust, creating spaces, building bridges, circulating capitals, and buffering relationships. Beneficiaries increased capacity for collective action is an outcome that becomes an alliance input, leading overtime to further benefits involving systemic change.